2001
DOI: 10.1002/ajim.1063
|View full text |Cite
|
Sign up to set email alerts
|

Capture–recapture estimation of unreported work‐related musculoskeletal disorders in Connecticut

Abstract: This analysis points to substantial under-reporting of MSD in Connecticut: estimates of unreported cases exceed those officially reported by a factor of 11:1. The findings have an important bearing on injury prevention programs and policy making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 33 publications
1
47
0
2
Order By: Relevance
“…Workers who consulted a specialist were eight times more likely to file for claims than those who only visited the company doctor. Morse et al [2001] interviewed 292 Connecticut residents with work-related musculoskeletal disorder among whom, 20.7% were reportedly covered by workers compensation. Of respondents seen by a general practitioner or a family doctor, 11-12% reported coverage by workers compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Workers who consulted a specialist were eight times more likely to file for claims than those who only visited the company doctor. Morse et al [2001] interviewed 292 Connecticut residents with work-related musculoskeletal disorder among whom, 20.7% were reportedly covered by workers compensation. Of respondents seen by a general practitioner or a family doctor, 11-12% reported coverage by workers compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for under-reporting of occupational illness and MSD has been growing [Biddle et al, 1998;Pransky et al, 1999;Rosenman et al, 2000;Morse et al, 2001]. Azaroff et al [2002] provide a conceptual model of filters that block recognition and reporting, including a worker reporting an illness to the supervisor (fear of retribution, immigration status concerns, thinking it was not a serious enough illness), a physician diagnosing the condition as work-related (lack of training in occupational medicine), lost time from work, and the employer recording the condition (concern about compensation rates, OSHA inspections, lack of knowledge of recording laws).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 2/3 of OSHAs occupational disease category is due to Musculoskeletal Disorders (MSD) [termed ''repetitive trauma'' by the Bureau of Labor Statistics (BLS)]. Recent studies have found that MSD are substantially under-reported, though the distribution by company size has not been reported [Biddle et al, 1998;Pransky et al, 1999;Rosenman et al, 2000;Morse et al, 2001].…”
Section: Introductionmentioning
confidence: 97%
“…(2) Additionally, it has been reported that many MSDs are underreported, raising the number of cases that may actually be occurring in the workplace. (3,4) The nature of work in the construction industry often varies in its work conditions (residential vs. commercial, weather), job sites (workers may work at multiple sites and geographical locations), and employers (workers often have multiple employers). The variable conditions inherent in construction work make it difficult to determine the association between working conditions and MSDs.…”
Section: Symptoms Of Musculoskeletal Disorders Among Apprentice Constmentioning
confidence: 99%